The Relationship Between Double Taxation Avoidance Agreement (P3B) And Digital Tax (Case Study Of Indonesia And Singapore) - Afia Zuchri (UNIVED Press, 2025)
This study examines the relationship between Double Taxation Avoidance Agreements (DTAs) and digital taxation in the context of the rapidly growing digital economy in Indonesia and Singapore. With the increasing digital economic activity, companies such as Google, Amazon, Netflix operate in multiple countries without a significant physical presence, posing challenges to the traditional taxation system based on the nexus principle (OECD, 2015). DTAs, as the main instrument for avoiding double taxation, often rely on the concept of Permanent Establishment (PE), which is becoming less relevant in the context of digital transactions (Avi-Yonah, 2007). Through a qualitative approach, this study analyzes the provisions in DTAs relating to digital taxation, as well as the challenges faced by both countries in their implementation. This study also identifies obstacles that arise due to the incompatibility between DTA provisions and the characteristics of the digital economy, such as the ambiguity in the definition of royalties and technical services (Chen, 2022). In addition, this study explores the digital tax policies implemented in Indonesia, including VAT and Income Tax (PPh) on digital income, as well as the Digital Services Tax (DST) proposed by Singapore (Flegg & Sinclair, 2021). The results of the study indicate that without any revision to the clauses in the P3B, both countries will face difficulties in collecting taxes fairly and effectively on income generated from cross-border digital transactions. This study recommends the need for adaptation of the P3B to include provisions that are more relevant to the digital economy, as well as international collaboration in formulating tax policies that can address global tax challenges (Kraus & Morris, 2021). Thus, this study is expected to make a significant contribution to the international tax literature and provide insights for policymakers in dealing with tax issues in the ever-evolving digital era.